PENGARUH PRICE EARNING RATIO, PRICE TO BOOK VALUE RATIO, DEBT TO EQUITY RATIO, RETURN ON EQUITY DAN SIZE TERHADAP RETURN SAHAM PADA PERIODE BULLISH (Survei PadaPerusahaan Manufaktur di Bursa Efek Indonesia Periode 2006-2007) - Animah Animah (Universitas Jember, 2010)
The objective of this research was to know the impact of Price Earning Ratio, Price To Book Value Ratio, Debt To Equity Ratio, Return On Equity dan Sizeto the stock return period bullish. This research uses purposive sampling method with judgment and conducted for 27 manufacturing companies listed in the Jakarta Stock Exchange during the period 2006-2007. The data was analysed by using multiple linear regression. The results showed that there is significant influence simultaneously (21.2%) and partially significant for the price earning ratio variable which is shown by the significance value of 0,05%. The results also show that other variables such as Price To Book Value Ratio, Debt To Equity Ratio, Return On Equity dan Sizeis not significant to the stock return period bullish. For the next researcher, it is suggested to add another variable like debt to asset ratio, Current ratio,Earning yieldand to expand the population (all go public companies). Keywords: price earning ratio, price to book value ratio, debt to equity ratio, return on equity, size, stock return